PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW UNTUK MENINGKATKAN HASIL BELAJAR BIOLOGI PESERTA DIDIK KELAS XII MIPA 2 SMA NEGERI 1 KUTA UTARA - Ni Luh Putu Pitri Ramanti Dewi; I Komang Sukendra (LP3M Universitas PGRI Mahadewa Indonesia, 2023)
Cooperative learning model with Jigsaw Type is a model that can be applied to guide students to be more active and help each other in discussed with the jigsaw type, namely the home group and the original group. The purpose of this study is to improve student learning outcomes with the jigsaw type cooperative learning model in biology subjects on mutation material. This type of research is classroom action research. The research subjects were class XII MIPA 2 students and the object of research was the learning outcomes of students in biology subjects on mutation material on the application of the jigsaw cooperative learning model. This research consists of four stages, namely (1) Planning; (2) Actions; (3) Observation; (4) Reflection. Data collection techniques using the description test method. The results of the study show that applying the jigsaw cooperative learning model can improve student learning outcomes in biology subject matter for class XII MIPA 2 mutations at SMA Negeri 1 North Kuta in the 2022/2023 academic year.